İTİBAR YÖNETİMİ KONULU LİSANSÜSTÜ TEZLERİN BİBLİYOMETRİK ANALİZİ. - ÖZGÜR, Ömer Faruk (Journal of Social Sciences Institute / Sosyal Bilimler Enstitüsü Dergisi)
The issue of reputation has received special attention in the academic field, especially after the 2000s. Both management science and public relations academicians have conducted studies on how reputation is formed, how it can be measured and how it can be managed. In this study, 77 master's and doctoral theses related to reputation management in postgraduate academic studies in Turkey were subjected to bibliometric analysis. Thus, it was aimed to reveal a general view of academic studies on reputation management in Turkey. There was a significant increase in the number of theses submitted in 2010 and 2019. As a result, it was determined that most of the theses were prepared at Marmara University. It has been observed that the subject of reputation management has been studied in the context of the public relations department rather than the management science department. It has been observed that quantitative methods and questionnaires as data collection tools are mostly preferred in studies on reputation. Then, it was determined that the most frequently preferred methods were the qualitative method, indepth interview technique and case study technique. When we look at the most frequently cited sources in the theses, the names Fombrun, Davies, Chun stand out in the international literature, while Kadıbeşegil, Ural, Okay, Peltekoğlu, Dörtok stand out among the Turkish names. It is thought that this study, which highlights the situation in Turkey regarding postgraduate theses related to reputation management, will contribute to reducing the lack of literature review in the field and will be a preliminary preparation for future studies on reputation management.